Control of the cyclic GMP phosphodiesterase of frog photoreceptor membranes (The Rockefeller University Press, 1980)
The light-activated cyclic GMP phosphodiesterase (PDE) of frog photoreceptor membranes has been assayed in isolated outer segments suspended in a low-calcium Ringer's solution. Activation occurs over a range of light intensity that also causes a decrease in the permeability, cyclic GMP levels, and GTP levels of isolated outer segments. At intermediate intensities, PDE activity assumes constant intermediate values determined by the rate of rhodopsin bleaching. Washing causes an increase in maximal enzyme activity. Increasing light intensity from darkness to a level bleaching 5 x 10(3) rhodopsin molecules per outer segment per second shifts the apparent Michaelis constant (Km) from 100 to 900 microM. Maximum enzyme velocity increases at least 10-fold. The component that normally regulates this light- induced increase in the Km of PDE is removed by the customary sucrose flotation procedures. The presence of 10(-3) M Ca++ increases the light sensitivity of PDE, and maximal activation is caused by illumination bleaching only 5 x 10(2) rhodopsin molecules per outer segment per second. Calcium acts by increasing enzyme velocity while having little influence on Km. The effect of calcium appears to require a labile component, sensitive to aging of the outer segment preparation. The decrease in the light sensitivity of PDE that can be observed upon lowering the calcium concentration may be related to the desensitization of the permeability change mechanism that occurs during light adaptation of rod photoreceptors.